Penerapan Strategic Marketing Pada Bank Syariah Mandiri Kantor Cabang Jemur Handayani Surabaya - Aprilia Kinasih Putri Ramadhani; Ari Prasetyo (Universitas Airlangga, 2014)
Islamic Banking in Indonesia are developing rapidly. it can be seen by the number of offices that increase from year to year. This development of islamic banking can make a competition between the islamic banking. Therefore, to face the tight competition, islamic banking needs the right strategic marketing that compatible with sharia principle. The strategic marketing consists of three components. They are segmenting, targeting, and positioning. This research aims to know how the application of strategic marketing in Bank Syariah Mandiri Branch Office of Jemur Handayani Surabaya.This research is using qulitative approach with case study strategy. The datacollecting method is using direct interview with Bank Syariah Mandiri Branch Office of Jemur Handayani’s office workers. The data analysis method is using descriptive qualitative approach.The result of this research shows that strategic marketing which is applied in Bank Syariah Mandiri Branch Office of Jemur Handayani are compatible with sharia principle. Market segments in Bank Syariah Mandiri Branch Office of Jemur Handayani are from lending and funding. For targeting, Bank Syariah Mandiri Branch Office of Jemur Handayani is using the full market coverage pattern. And the positioning is done by raising the quality of service.